Monitoring and evaluation strategies for surgical task-shifting and task-sharing interventions: a scoping review - Binda, Catherine; Livergant, Rachel; Tersago, Jamie; Jami, Zainab; Chen, Le Q.; Birch, Leah; Blackman, Chloe; Chin, Esther; Wild, Hannah; Joos, Emilie; Joharifard, Shahrzad (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Task shifting and task sharing (TS/S) redistribute responsibilities across cadres to expand access to healthcare, particularly in underserved areas. TS/S addresses workforce shortages and improves the availability of essential surgical procedures. The scope and geographical distribution of surgical TS/S programs are well documented, less is known about how TS/S initiatives are monitored and evaluated, especially with respect to trainee, program, and health systems outcomes. This review describes existing approaches to evaluation within surgical TS/S initiatives. Methods We searched nine electronic databases (MEDLINE [Ovid], Embase [Ovid], CINAHL [EBSCO], Scopus, CABI Digital Library, Clarivate Web of Science, Evidence Aid, Global Index Medicus, and Eldis) on 31 January 2024 and 12 March 2025, using MeSH terms and keywords related to “Task Sharing” AND “Surgery”. All patient populations, practice settings, surgical skills, and study designs were eligible. No language or time restrictions were utilized. Publications that did not describe the evaluation of surgical skills, or that focused on skills within a practitioner’s typical scope of practice, were excluded. Two reviewers independently screened and extracted data. Risk of bias was assessed with MINORS. Findings were synthesized using inductive content analysis. Results were tabulated and presented graphically. Results Of 2483 identified records, 1609 unique publications were screened, 452 underwent full-text review, and 228 were included in the review. Most studies reported surgical TS/S in low-income countries (41.7%, 95/228). Obstetric and gynaecological procedures were most commonly taught (61.4%, 140/228). In total, 1753 examples of evaluation metrics were extracted from the 228 included publications. The evaluation metrics were sorted into three themes, including metrics that evaluated TS/S providers (72.6%, 1272/1753), training programs (7.5%, 132/1753), and systems (19.9%, 349/1753). Conclusion This scoping review comprehensively describes existing evaluation strategies. While evaluation of surgical TS/S initiatives remains heterogeneous, limiting the generalizability of any single approach, we successfully grouped monitoring and evaluation metrics into three key domains: provider, program, and health systems. Future work should focus on proposing a comprehensive but adaptable monitoring and evaluation framework that can be used by surgical TS/S programs across the globe.